2016
DOI: 10.1002/acr.22857
|View full text |Cite
|
Sign up to set email alerts
|

Does Renin‐Angiotensin System Blockade Protect Lupus Nephritis Patients From Atherosclerotic Cardiovascular Events? A Case–Control Study

Abstract: Our data do not support the hypothesis that ACE inhibitors/ARBs may be protective against atherosclerotic CVEs in LN patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“… 114 117 In the single prospective trial that explored the possible atheroprotective effect of ACE inhibitors and angiotensin receptor blockers in patients with LN, there was no difference in the cumulative occurrence of CVD between the treatment and the control arm (p = 0.7). 118 The increased risk for infections in patients with LN is supported by a number of studies (HR: 1.4–5.3) 119 122 ; regarding treatment-related risk factors, a network meta-analysis of 32 RCTs identified that high-dose GC therapy was associated with the highest risk for serious infections compared to TAC as reference drug (OR 12.8, 95% CI 1.53 to 119.90), followed by low-dose CY (OR 4.8, 95% CI 1.48 to 17.64) and high-dose CY (OR 6.6, 95% 2.25 to 20.50). 123 …”
Section: Resultsmentioning
confidence: 99%
“… 114 117 In the single prospective trial that explored the possible atheroprotective effect of ACE inhibitors and angiotensin receptor blockers in patients with LN, there was no difference in the cumulative occurrence of CVD between the treatment and the control arm (p = 0.7). 118 The increased risk for infections in patients with LN is supported by a number of studies (HR: 1.4–5.3) 119 122 ; regarding treatment-related risk factors, a network meta-analysis of 32 RCTs identified that high-dose GC therapy was associated with the highest risk for serious infections compared to TAC as reference drug (OR 12.8, 95% CI 1.53 to 119.90), followed by low-dose CY (OR 4.8, 95% CI 1.48 to 17.64) and high-dose CY (OR 6.6, 95% 2.25 to 20.50). 123 …”
Section: Resultsmentioning
confidence: 99%
“…Despite this possible contribution for atherosclerosis development, only few studies have focused on the potentially protective role of ACEIs and ARBs in SLE. A non-randomized prospective trial, comprising 144 patients with lupus nephritis treated with ACEIs/ARBs and 301 non-treated patients, showed no significant differences in the cumulative occurrence of CVE between the groups ( 160 ). One cross-sectional study comprising 51 SLE patients, mainly African-American, of whom only 12 were being treated with ACEIs, showed a strong association between total plaque area and 25(OH)-vitamin D insufficiency or ACEI non-use ( 161 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, traditional risk factors for cardiovascular events including age, gender, smoking, hypertension, and dyslipidemia have been correlated with but cannot fully explain the exacerbated atherogenesis in SLE and RA patients (Bruce et al, 2003;Castañeda et al, 2015;Esdaile et al, 2001). While the serum type-I IFN activity is independently associated with biomarkers of atherosclerosis development in lupus patients (Somers et al, 2012), some studies reported that preventive therapies for traditional risk factors, such as hypercholesterolemia and hypertension, failed to significantly reduce the incidence of CVDs in lupus patients (Petri et al, 2011;Schanberg et al, 2012;Tselios et al, 2016;Wigren et al, 2015). Notably, increased subclinical atherosclerosis prevalence is observed in individuals with primary (i.e., antineutrophil cytoplasmic antibody-associated vasculitis) or secondary (i.e., associated with SLE or RA) vasculitis (Argyropoulou et al, 2018;Chironi et al, 2007;Guillevin and Dörner, 2007).…”
Section: Clinical Implications and Cardiovascular Manifestationsmentioning
confidence: 99%